2020
DOI: 10.1186/s13045-020-00961-8
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the assessment of minimal residual disease in mantle cell lymphoma

Abstract: The clinical impact of minimal residual disease detection at early time points or during follow-ups has been shown to accurately predict relapses among patients with lymphomas, mainly in follicular and diffuse large B cell lymphoma. The field of minimal residual disease testing in mantle cell lymphoma is still evolving but has great impact in determining the prognosis. Flow cytometry and polymerase chain reaction-based testing are most commonly used methods in practice; however, these methods are not sensitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 76 publications
0
19
0
Order By: Relevance
“…The cMCL subtype generally exhibits an unmutated or minimally mutated CDR3 region [ 54 ]. The core mechanism in the malignant transformation of MCL has been demonstrated to be a translocation involving chromosomes 11 and 14 (t(11;14)(q13,32), CCND1 /IGH), leading to the overexpression of CCND1 protein [ 5 , 61 , 62 ], while other cases may be driven by a CCND2 or CCND3 translocation with IGK or IGL [ 63 ]. Aberrant translocation events in MCL can occur in V(D)J recombination, SHM, or CSR based on the DSBs formed during these processes [ 44 ].…”
Section: The Oncogenesis Of B-lineage Malignancies and The Correspond...mentioning
confidence: 99%
See 1 more Smart Citation
“…The cMCL subtype generally exhibits an unmutated or minimally mutated CDR3 region [ 54 ]. The core mechanism in the malignant transformation of MCL has been demonstrated to be a translocation involving chromosomes 11 and 14 (t(11;14)(q13,32), CCND1 /IGH), leading to the overexpression of CCND1 protein [ 5 , 61 , 62 ], while other cases may be driven by a CCND2 or CCND3 translocation with IGK or IGL [ 63 ]. Aberrant translocation events in MCL can occur in V(D)J recombination, SHM, or CSR based on the DSBs formed during these processes [ 44 ].…”
Section: The Oncogenesis Of B-lineage Malignancies and The Correspond...mentioning
confidence: 99%
“…After the initial diagnosis of B-lineage malignancy was confirmed by clinical symptoms, imaging manifestations, and histopathological examinations, the BM aspirate samples were preserved and subjected to high-throughput sequencing. Index clones were identified in these samples by the following criteria: (1) the proportion of index clones needs to be at least 3% of all sequences at the specific locus, (2) the frequency of cells that carry index clones needs to be at least 0.2% of all nucleated cells [ 5 ], and (3) other criteria in kits designed by different companies [ 14 ]. By using the algorithm of exact match and up to 2-bp mismatches, the disease clones in follow-up samples were compared with the initial index clones in diagnostic samples, based on which the presence or absence of MRD was identified, and the quantity of MRD was calculated [ 18 ].…”
Section: Mrd Monitoring Through Clonality Assessment By Ngsmentioning
confidence: 99%
“…cIg DNA is routinely used on tissue biopsies to aid in the diagnosis of lymphoma and is increasingly being assessed in plasma cfDNA as a disease monitoring marker, particularly for mantle cell lymphoma. 29 However, the analysis of cIg DNA in cfDNA has not previously been used to facilitate the diagnosis of lymphoma. Traditionally, definitive diagnosis requires a biopsy of suspicious lesions identified by physical examination and/or imaging during the healthcare practitioner interval.…”
Section: Discussionmentioning
confidence: 99%
“…Its management is variable, depending on the risk and patient performance status, and includes chemotherapy, immunotherapy, or autologous stem cell transplantation. The MRD is not very standardized, although some studies have been conducted using the PCR amplification of IgH rearrangements, demonstrating an impact on the clinical outcomes of the patient after autologous transplantation [ 114 , 115 , 116 ]. Lakhotia et al used NGS to detect Ig heavy and light chains, and CCND1 and BCL2 gene mutations in ctDNA; they concluded that the baseline ctDNA correlated with the total metabolic tumor volume on the PET scans, and the clearance of ctDNA after one cycle of DA-EPOCH-R + BZ was strongly associated with a superior median PFS (76.4 vs. 20.7 months, p = 0.0037) and a trend toward a superior four-year overall survival (OS) (92.3% vs. 73.0%, p = 0.23).…”
Section: Lymphoid Malignanciesmentioning
confidence: 99%